2020
DOI: 10.1002/jbmr.4213
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Exercise Intervention Program on Bone Health After Bariatric Surgery: A Randomized Controlled Trial

Abstract: Exercise has been suggested as a therapeutic approach to attenuate bone loss induced by bariatric surgery (BS), but its effectiveness remains unclear. Our aim was to determine if an exercise‐training program could induce benefits on bone mass after BS. Eighty‐four patients, submitted to gastric bypass or sleeve gastrectomy, were randomized to either exercise (EG) or control group (CG). One month post‐BS, EG underwent a 11‐month supervised multicomponent exercise program, while CG received only standard medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(83 citation statements)
references
References 44 publications
0
80
0
1
Order By: Relevance
“…27,49 The meta-analysis of these two reviews showed a lower weight regain in the exercise group, with an MD between groups of 4.7 kg [95% CI: A more recent study reported similar findings. 63 This is likely to be an important benefit of exercise training given the increased risk of fracture that has been reported after bariatric surgery, especially after gastric bypass surgery. 64 The effects of exercise on cardiometabolic health are less conclusive in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…27,49 The meta-analysis of these two reviews showed a lower weight regain in the exercise group, with an MD between groups of 4.7 kg [95% CI: A more recent study reported similar findings. 63 This is likely to be an important benefit of exercise training given the increased risk of fracture that has been reported after bariatric surgery, especially after gastric bypass surgery. 64 The effects of exercise on cardiometabolic health are less conclusive in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…34,35,42,52,54,55 Most (k=18, 64.3%) studies had samples comprising ≥75% women 32-34, 36, 37, 39-47, 49, 54, 56, 58 and 21.4% (k=6) comprised only women. 35,38,48,[51][52][53] Beyond providing data on age and sex/gender, 39.3% (k=11) of articles reported other sociodemographic data, 30,32,33,35,39,44,45,49,51,52,56 and 42.9% (k=12) reported comorbidities prevalence. 32, 33, 35, 36, 39, 46, 49, 51-53, 56, 58 Among the 6 articles (21.4%) reporting ethnicity/race, all had samples comprising ≥50% White participants.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…30, 34-39, 42-45, 47, 48, 50-53, 55-13 58 Most (k=16, 57.1%) lasted ≤13 weeks (range 4-104 weeks), 32, 33, 35, 38, 40-46, 52, 55-58 89.3% (k=25) were supervised exercise, 30, 32-37, 39-41, 43-54, 56-58 and 35.7% (k=10) held sessions individually. 30, 32, 35, 36, 41-43, 51, 56, 57 Exercise sessions were performed: in hospitals, clinics, or medical centers (k=10, 35.7%), 33,40,43,49,[51][52][53][56][57][58] at home (k=4, 14.3%), 30,36,41,42 in research centers (k=3, 10.7%), 35,46,47 in community or fitness centers (k=3, 10.7%), 44,50,54 or at a facility (k=3, 10.7%), 32,39,45 location was not specified in 17.9% (k=5) of articles. 34,37,38,48,55 Most (k=19, 67.9%) interventions initiated after bariatric surgery started during the first year after the surgery was performed, 30, 34-39, 42-44, 48, 50-53, 55-58 ranging from 0 to 36 months after bariatric surgery.…”
Section: Exercise Intervention Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations